2021
DOI: 10.18778/1730-2366.16.10
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles – possible applications and threats

Abstract: Silver is known for its biocidal properties. This metal has been used for decorations and food preservation since ancient times and has also been used in medicine. Silver foil has been used to cover wounds and burns. In addition, silver solutions were created to help fight the microorganisms responsible for causing infections, which helped the wound healing process. Currently, to increase and optimize the properties of silver, it is used on a nanometric scale. Nanosilver, due to its expanded spectrum of proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Gram-positive bacteria are more sensitive to silver than Gram-negative bacteria, which results from the fact that the presence of more layers of peptidoglycan reduces sensitivity of these cells. In addition, studies have shown that the formation of AgNPs combinations with commonly used antibiotics increases their effect [ 3 , 19 , 20 ]. Due to their antimicrobial properties, AgNPs are popular agents used in production of cleaning and disinfecting agents for surfaces and textiles, gels, or antimicrobial paints, as well as food packaging and preservation materials.…”
Section: Introductionmentioning
confidence: 99%
“…Gram-positive bacteria are more sensitive to silver than Gram-negative bacteria, which results from the fact that the presence of more layers of peptidoglycan reduces sensitivity of these cells. In addition, studies have shown that the formation of AgNPs combinations with commonly used antibiotics increases their effect [ 3 , 19 , 20 ]. Due to their antimicrobial properties, AgNPs are popular agents used in production of cleaning and disinfecting agents for surfaces and textiles, gels, or antimicrobial paints, as well as food packaging and preservation materials.…”
Section: Introductionmentioning
confidence: 99%